Effect of flight level to maximum power utilization for PEMFC/supercapacitor hybrid uav with switched reluctance motor thruster - Oksuztepe, Eyyup; Bayrak, Zehra Ural; Kaya, Ufuk (Pergamon-Elsevier Science Ltd, 2023)
In this study, the performance of a fixed-wing PEMFC/SC hybrid UAV with an SRM thruster is investigated by different flight levels. Flight levels negatively affect the PEMFC due to changing ambient conditions such as air temperature and pressure. Hence, the international standard atmosphere (ISA) model for PEMFC voltage-current-power ratings is derived with 100 m intervals for 0-7500 m. The demanded electrical power by UAV increases at high altitudes due to the compressor used for air pressurization of PEMFC. Therefore, a maximum power point tracking (MPPT) model of PEMFC should be utilized in case of overshooting the maximum power level that can be provided. While the main power source of the UAV is PEMFC, the auxiliary power source is SC. The SC is preferred for DC bus voltage stabilization, avoiding maximum power point overshoot, and preventing high instantaneous current that shortens the lifespan of PEMFC. The proposed UAV model is verified at MATLAB/Simulink and the results prove that the system is satisfying.(c) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: UAV; PEMFC; 4-phase switched reluctance motor; Supercapacitor; MPPT; Energy management